Brazil`s travel report December 3-23, 1972 - Díaz, R.O. (International Center for Tropical Agriculture, 1972)
This report compiles people and institutions involved in cassava production and processing in Brazil and lists bibliographical references of literature found in some libraries and documentation centers, Statistical data obtained from these publications are given on production costs, area planted, yields, exports, uses, labor inputs, current prices and future tendencies. (AS)